2013
DOI: 10.7455/ijfs/2.2.2013.a1
|View full text |Cite
|
Sign up to set email alerts
|

Profile of currently employed European Food Scientists and Technologists: Education, experience and skills

Abstract: The food & drink (F&D) sector in Europe ranks low in innovation and the European F&D industry has been losing importance in the global market. The food professionals, i.e., food scientists and technologists (FSTs), may not be meeting the varied demands of the sector. Here, we identify education, experience and skills of current FSTs and compare  geographic regions and employment areas. Between 2009 and 2012, 287 questionnaires representing over 4000 FSTs were collected from employers in 16 countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Similar movements were also observed in different parts of the world, such as Europe, Americas and Oceania (Alves, Restivo, & da Silva, 2015;Borrego & Bernhard, 2011). It is interesting to note, however, that despite this, in the European Union, Flynn, Bejarano, Wahnstrom, Echim, and Quintas (2013) carried out a profile analysis of professionals in the field of Food Science and Technology in order to analyse why the sector exhibits low innovation rates when compared to other industries. Flynn et al (2013) suggested that the education of these professionals is on track.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…Similar movements were also observed in different parts of the world, such as Europe, Americas and Oceania (Alves, Restivo, & da Silva, 2015;Borrego & Bernhard, 2011). It is interesting to note, however, that despite this, in the European Union, Flynn, Bejarano, Wahnstrom, Echim, and Quintas (2013) carried out a profile analysis of professionals in the field of Food Science and Technology in order to analyse why the sector exhibits low innovation rates when compared to other industries. Flynn et al (2013) suggested that the education of these professionals is on track.…”
Section: Introductionmentioning
confidence: 60%
“…As observed by Roos et al (2016) and Flynn et al (2013), the approach of academia and industry proves to be a determining factor in the professional training of the engineer.…”
Section: Ijfsmentioning
confidence: 91%
See 2 more Smart Citations
“…A survey of skills most desired by European employers in the food and drink sector showed communication to be the single most sought after skill (Flynn, Ruiz-Bejarano, et al, 2013). In the chemical industry, high level representatives listed communication as the number 1 personal skill for engineers (CEFIC, 2009) and, in Australia, communication is being integrated into some university engineering courses (Armstrong & Baillie, 2011).…”
Section: Satisfaction With Soft Skillsmentioning
confidence: 99%